2016
DOI: 10.1007/s10681-016-1741-z
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between SPAD value and grain yield can be affected by cultivar, environment and soil nitrogen content in wheat

Abstract: 10 Abstract SPAD-502 (Minolta Ltd, Osaka Japan), a 11 hand-held chlorophyll meter is widely used in the 12 synchronization of N supply with actual crop demand, 13 however it is also known, that genotype and environ-14 ment may effect SPAD value. Consequently, the aim of 15 this study was to evaluate the genetic and environ-16 mental variation in SPAD value and to determine the 17 relationship between SPAD value at heading (GS 59) 18 and grain yield. Field experiments were conducted in 19 three consecutive crop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
52
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(63 citation statements)
references
References 27 publications
8
52
0
3
Order By: Relevance
“…There were differences between cultivars, for equivalent N treatments, of measurements made with the SPAD-502 and MC-100 chlorophyll meters, when the N supply was sufficient and excessive (N2 and N3 treatments), but not when the N supply was deficient (N1 treatment). There are previous reports of cultivar notably affecting SPAD measurements in wheat [30] and rice [32]. For the vegetation indices measured with the Crop Circle ACS-470 reflectance sensor, there were no consistent significant differences between cultivars.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…There were differences between cultivars, for equivalent N treatments, of measurements made with the SPAD-502 and MC-100 chlorophyll meters, when the N supply was sufficient and excessive (N2 and N3 treatments), but not when the N supply was deficient (N1 treatment). There are previous reports of cultivar notably affecting SPAD measurements in wheat [30] and rice [32]. For the vegetation indices measured with the Crop Circle ACS-470 reflectance sensor, there were no consistent significant differences between cultivars.…”
Section: Discussionmentioning
confidence: 57%
“…Most of the research with proximal optical sensors to assess crop N status has been with a specific cultivar of a given species. Few reports have examined how differences between cultivars affect optical sensor measurements.Working with wheat, Monostori et al [30], reported that cultivar had a notable effect on the relationship between chlorophyll meter (SPAD-502) readings and grain yield. Similar results with wheat were obtained by Hoel [31] using the Hydro N-Tester chlorophyll meter.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it is only measured in the flag leaf, not across the canopy. Based on similar results, Monostori et al [79] concluded that relative chlorophyll content values should be calibrated according to the cultivars used and depending on their performance. On the other hand, chlorophyll measurements derived from the RGB and multispectral images did show some significant correlations with GY.…”
Section: Ability Of the Remote Sensing Measurements To Assess Genotypmentioning
confidence: 95%
“…Replacement seedlings were used from substrates with equivalent %BC but no pH adjustment and were Weekly measurements over 9 weeks were taken for plant height and for relative chlorophyll content as leaf greenness using a SPAD 502 Plus Chlorophyll Meter (Spectrum Technologies, Inc., Aurora, IL). SPAD meters measure the difference between red light (540 nm) and infrared light (940 nm) absorbance, and for a given species and cultivar under the same growing conditions (e.g., light, water availability) SPAD values can be used as an indicator of relative chlorophyll content (Monostori et al, 2016;Xiong et al, 2015). To ensure accurate measurement of new leaf tissue, four separate points were consistently measured on the second fully extended leaf from the top of the plant (apical meristem) (Bi et al, 2010;Wang et al, 2014;Yuan et al, 2016).…”
Section: Plant Growth Experimentsmentioning
confidence: 99%